REVIEW: TOXICITY, NATURAL AND INDUCED DEGRADATION OF CHLORPYRIFOS - PRITI BANSAL; Dhiraj Sud; Jitesh Kumar (Journal of the Chilean Chemical Society, 2020)
The increase in demand for agricultural products due to the growing population led to excessive inputs of pesticides in the agriculture field which resulted in contamination of the environmental segments of life i.e. air, water, and soil. Chlorpyrifos is one of the most extensively used broad-spectrum organophosphate insecticides. The usage and broad-spectrum applicability of chlorpyrifos lead to widespread contamination in the environment and serious damage to non-target organisms. Moreover, metabolites of chlorpyrifos i.e. chlorpyrifos-oxon and 3,5,6-trichloro-2-pyridinol are found to be more toxic than its parent compound. This review emphasizes on various toxic effects of chlorpyrifos and its metabolites on living organisms. The efforts put to develop the efficient methods for the degradation of the insecticide in soil and water i.e. photocatalytic, biodegradation, electrochemical and others have been discussed. Analytical techniques used for the study of degraded products and various intermediates formed during degradation under different conditions are summarized. It also includes the general pathway for the degradation of chlorpyrifos. The review will help in the development of tools for degradation and mineralization of organophosphate pesticides by knowing the mechanism of degradation and applicability of the developed process at a large scale.